Promoting global health innovation: On the need for global health care solutions in the spirit of the International Conference on Applied Science and Health (ICASH) - Andrew John Macnab (GHMJ (Global Health Management Journal), 2017)
The generation and testing of novel ideas by young investigators is an important mechanism for driving scientific and social innovation. Especially where these ideas are bold and involve new approaches or forms of cooperation that can contribute to sustainable health improvements for society. The sharing of such ideas and exchange of knowledge and experience by young investigators was the aim of the first International Conference on Applied Science and Health (ICASH) held in Bangkok in February 2017. ICASH was a joint initiative designed by the Institute of Population and Social Research at Mahidol University,Thailand, the Doctoral Program in Public Health Science at Diponegoro University, Indonesia, and Universitas ‘Aisyiyah Yogyakarta, Indonesia.ICASH brought together experts, practitioners, professionals and students from applied science and health related fields, and what they shared is available in the published conference proceedings registered at National Library of Indonesia and available at <http://publications.inschool.id/index.php/icash/index> The Global Health Management Journal was established by the founders of ICASH to be a platform for presenting the outcome of projects intended to define where scientific, educational, technological and social innovation can be applied to improve health. This first edition highlights five of the presentations made at the first International Conference on Applied Science and Health (ICASH 2017). The selected papers from the conference were double-blindly reviewed and published in this first editorial of GHMJ. The journal will be valuable in this regard, as it will provide a forum for young investigators to describe bold scientific ideas and social innovations able to save and improve lives alongside reports of new forms of cooperation and effective health services delivery. This combination of innovations that integrate science and technology with education and social change together will meet the recognized need for greater understanding of "what works and why” and in turn contribute to more sustainable health improvements for society as a whole.